Eco-Friendly Biopolymer Management For Sustainable Plastic Solutions: Applications, Challenges, And Implementation Strategies - Muhammad Sadali; Muhammad Taufiq Abadi; Muhammad Akbar Fadzkurrahman A (International Journal of Science and Environment (IJSE), 2025)
The use of single-use plastics derived from fossil fuels has been a major cause of environmental pollution. As a solution, biopolymers based on renewable resources have emerged as an environmentally friendly alternative. This article examines the development, challenges, and implementation strategies for biopolymers in providing sustainable plastic solutions. The discussion begins with an introduction to biopolymers, their types, and applications in replacing fossil-based plastics in various industrial sectors. It is found that although biopolymers offer environmental advantages, key challenges include higher production costs, limited raw materials, and waste management. The article also discusses the role of government policies, technological innovation, and multisectoral collaboration in accelerating biopolymer adoption. With appropriate policies, infrastructure development, and increased consumer awareness, Indonesia has great potential to lead sustainable biopolymer production.